Settlement Policies and the Economic Success of Immigrants - Per-Anders Edin; Peter Fredriksson; Olof Åslund (Uppsala University, Department of Economics, 2000)
Many developed countries, e.g. the UK, Germany, and Sweden, use or have used settlement policies to direct the inflow of new immigrants away from immigrant dense metropolitan areas. We evaluate a reform of Swedish immigration policy that featured dispersion of refugee immigrants across the country, but also a change in the approach to labor market integration. We focus exclusively on how immigrants fared because of the policy. The results indicate that immigrants experienced fairly substantial long run losses because of the policy. We also find that only a smaller share of this effect was associated with the dispersion of immigrants across regions. The larger share of the impact appears to stem from a common component that affected immigrants regardless of where they were located. Our somewhat speculative reading of this result is that it can be traced to a shift in emphasis of integration policy from a policy focusing on labor market assimilation to one of income support.
urn:nbn:se:uu:diva-2506
Keywords: J15; J18; R23; 330; Immigration; Settlement policies; Labor market outcomes; Einwanderung; Niederlassungsrecht; Wirkungsanalyse; Schweden